2016
DOI: 10.4257/oeco.2016.2002.07
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition, Conservation Status, and Sources of Threat of Anurans in Mosaics of Highland Grasslands of Southern and Southeastern Brazil

Abstract: Amphibians are the most threatened vertebrate group in the world, with about 32% of species under some category of threat. Conservation strategies depend on basic data, such as species distribution and natural history, which are largely lacking for endemic species inhabiting mosaics of highland grasslands and forest patches of Southern and Southeastern Brazil. Highland grassland fields occur in the Serra do Mar ecoregion and harbor an endemic anuran fauna associated to rocky outcrops and open fields interspers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…In fact, some studies have suggested that the Rapoport effect is not widespread along either latitudinal or altitudinal gradients, and thus would have limited predictive power for analyses of spatial distribution of species (McCain & Knight, 2013;Ribas & Schoereder, 2006;Rohde et al, 1993). In the specific case of the Atlantic Forest frogs, the lack of support for the Rapoport rule may result from the fact that many of the species found at higher altitudes are habitat-specialists or microendemics, and thus have small altitudinal ranges (Cruz & Feio, 2007;Garey & Provete, 2016), as also reported for other tropical mountain ranges, such as the Andes (Bernal & Lynch, 2008;Navas, 2006). The apparent influence of high-altitude endemism on distribution patterns reflects the general tendency found in ectothermic vertebrates (Laurance et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, some studies have suggested that the Rapoport effect is not widespread along either latitudinal or altitudinal gradients, and thus would have limited predictive power for analyses of spatial distribution of species (McCain & Knight, 2013;Ribas & Schoereder, 2006;Rohde et al, 1993). In the specific case of the Atlantic Forest frogs, the lack of support for the Rapoport rule may result from the fact that many of the species found at higher altitudes are habitat-specialists or microendemics, and thus have small altitudinal ranges (Cruz & Feio, 2007;Garey & Provete, 2016), as also reported for other tropical mountain ranges, such as the Andes (Bernal & Lynch, 2008;Navas, 2006). The apparent influence of high-altitude endemism on distribution patterns reflects the general tendency found in ectothermic vertebrates (Laurance et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The regional gradient had an upper limit 400 m higher than that of the local gradient, which did not exceed 1900 m a.s.l. Areas above this altitude in the Serra do Mar are dominated by upper montane grasslands known as “campos de altitude” (Mallet‐Rodrigues et al, 2010; Safford, 1999a), which tend to be species‐poor compared to forested areas, particularly regarding anuran amphibians (Folly et al, 2016; Garey & Provete, 2016). This would account for the long “tail” at the right‐hand end of all three graphs in Figure 2 (and a consequent lack of fit to the MDE model).…”
Section: Discussionmentioning
confidence: 99%
“…[See Scarano et al (2016) for summary of the plight of Brazilian high grasslands.] Additionally, fires are also plausible potential threats in high grasslands (Garey and Provete 2016). The species within the park seem free from chytrid fungus (Batrachochytrium dendrobatidis; Bd) (Rodriguez et al 2014), but the Bd cannot be ruled out as a potential threat (Garey and Provete 2016).…”
Section: Conservation Statusmentioning
confidence: 99%
“…Montane regions of the Brazilian Atlantic Forest biome (hereafter, AF) harbour a remarkable diversity of endemic plants, arthropods, birds and frogs (e.g. Garey & Provet, 2016; Vale et al., 2018). However, the AF is a highly threatened global biodiversity hotspot with only 26% of its original forest cover remaining, most of which scattered across thousands of fragments <50 ha (Rezende et al., 2018; Ribeiro et al., 2009).…”
Section: Introductionmentioning
confidence: 99%